4‐Benzamido‐TEMPO Catalyzed Oxidation of a Broad Range of Alcohols to the Carbonyl Compounds with NaBrO3 under Mild Conditions. Issue 5 (22nd May 2014) - Shen, Jiaxuan; Sun, Jiangkai; Qin, Shuangshuang; Chu, Changhu; Liu, Renhua
Abstract 4‐Benzamido‐TEMPO catalyzed oxidation system for conversion of a wide range of alcohols to the aldehydes or ketones with NaBrO3 under room temperature conditions has been developed. The credible, operationally convenient and economical, and condition mild oxidation protocol is particularly of interest in laboratory and in fine chemicals manufacture.